Effect of different work-to-rest ratios on physiological and perceptual responses to kickboxing specific high intensity intermittent exercise in elite male kickboxers - Bayram Ceylan; Furkan Öztürk; Hasan Basri Taskin; Ibrahim Ouergui; Bilgehan Baydil (Revista de Artes Marciales Asiáticas, 2025)
This study examined how different rest periods during high-intensity, intermittent kickboxing exercise affect physiological and perceptual responses in nine elite kickboxers. After being informed about the nature of the study, the athletes performed three exercise sessions consisting of kicks and punches with 1:1, 1:2 and 1:3 work-to-rest ratios in a randomised order, with 48 hours between each session. Their heart rate (HR) was measured at rest, immediately after, and six minutes after each exercise protocol. The athletes performed a countermovement jump (CMJ) test before and after exercise. Rating of perceived exertion (RPE) and muscle soreness (PMS) were measured immediately after exercise. The number of kicks and punches performed by the athletes was recorded.  Different rest ratios did not affect heart rate (F2, 14 = 1.08, p = 0.36). There was no difference in the number of kicks or punches performed by the athletes among different rest intervals (F2, 16 = 1.59, p = 0.24; F2, 16 = 1.70, p = 0.21). Exercises with different rest periods did not induce changes in CMJ (F₂,₁₆ = 0.69, p = 0.52). While the PMS responses of the athletes did not differ among the different rest intervals (F₂,₁₆ = 1.27, p = 0.31), the RPE values did differ among the exercises with the different rest intervals (F2, 16 = 3.70, p = 0.04). The athletes presented higher RPE values with the 1:1 interval than with the 1:2 and 1:3 intervals (p < 0.05). Kickboxing-specific HIIE with different rest intervals did not induce any physiological or performance differences, but led to a higher RPE following a short rest interval than a long one. These findings highlight that perceived difficulty (i.e. RPE) increases as the rest period shortens. Thus, there is a need to optimise HIIE protocols for targeted results and subjective recovery needs in this sport.